ANALISIS TINGKAT PENDAPATAN PKL DI WISATA MAZOOLA KECAMATAN PACIRAN KABUPATEN LAMONGAN - Ahmad Aziz Eka Putra; Dwi Susilowati; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2020)
Street vendors are traders which have minimum assets. They are engaged in productions and services. The activity aims to fulfill our needs or obtains salary. In this research, the incoming level of the street vendors are different and it is determined by some factors such as assets, experiences, and time. This study aims to analyze how the startup capital variable, experiences of the vendors, and the time working affect the incoming level at Maharani Zoo and Goa (Lamongan). The primary data in this study used questionnaire and interview directly to 30 respondents at Maharani Zoo and Goa (Lamongan). The author provides some questions to achieve the purposes and uses two methods such as income analysis method and multiple linear regression analysis; cross-section data model. Results of this study show that startup capital variable, experiences, and time working affect significant positive on the income of street vendors at Maharani Zoo and Goa (Lamongan).